Theoretical Review of the Implementation Islamic Boarding School Curriculum Management in Indonesia - Fathurrochman, Irwan; Danim, Sudarwan; Anwar AB, Syaiful; Kurniah, Nina; Hajja Ristianti, Dina (International Journal of Education Research and Development, 2021)
This study discusses a theoretical review of the implementation of Islamic boarding school curriculum management in Indonesia, based on the data that has been obtained, it can be concluded that Islamic boarding schools in Indonesia play an important role in the process of increasing the intelligence of productive age. This study uses a qualitative approach with descriptive analysis. Data collection techniques are carried out by literature review and literature study related to the management of the Islamic boarding school curriculum in Indonesia. Analysis of the data that has been collected is done by peeling, summarizing and collecting literature, so that it becomes a scientific research result. The results showed that of the thirty-four provinces in Indonesia there were 26,974 Islamic boarding schools and 12,668 educational units, with such a large number, the implementation of curriculum management is very important to do, novelty in this study it can be explained that planning, organizing, implementing, evaluating curriculum Islamic boarding schools in Indonesia have implemented the principles of modern management.